(untitled) (Economics and region, 2025)
The purpose of the article is to identify and analyze the key features of internal communication in the field of green tourism, as well as to formulate recommendations for increasing the efficiency of information exchange and personnel management taking into account environmental priorities. The object of the study is communication processes within organizations that provide services in the field of green tourism. The objectives of the work are: to investigate the fundamental principles and forms of internal communication, determine the main types of interaction, reveal the mechanisms for implementing environmental initiatives and substantiate the directions for further optimization of communication strategies. The article is devoted to the study of the features of internal communication in the field of green tourism and the justification of its importance in the context of sustainable development of the tourism industry. The role of internal communication as a strategic tool for coordinating actions and disseminating environmentally oriented values ​​among employees is considered. It was found that the effectiveness of internal interaction directly affects the quality of services provided, the level of tourist satisfaction and the ability of the organization to respond to challenges associated with the dynamics of environmental standards and consumer needs. The article offers practical recommendations for optimizing the internal information space, forming the environmental competence of personnel and stimulating a creative approach to solving environmental problems. It is emphasized that clear and transparent internal communication not only helps companies meet the growing demand for environmentally friendly services, but also contributes to the formation of a positive image and long-term competitiveness. Therefore, the results of the study are important not only for managers and specialists in the field of green tourism, but also for representatives of other industries interested in implementing environmentally responsible practices. The article outlines four essential principles of internal communication in green tourism, including environmental awareness and responsibility, transparency and openness, team synergy and innovation, flexibility and adaptation to change. It is determined that the implementation of these principles ensures the construction of a strong corporate culture focused on sustainable environmental results.